The Relation between Critical Thinking and Academic Compatibility among a Sample of Students of First Grade in Secondary School "A Field Study in Lattakia" (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
This study aimed to examine the relationship between critical thinking and academic compatibility among students of first grade in secondary school in Lattakia, and to investigate the differences in each of the critical thinking and academic compatibility variable depending on sex. The sample consisted of (90) students and It was chosen with equal stratified random sampling method, The Cornell Critical Thinking Test Level (x), and A Measure of Academic Compatibility were used in this study, the results showed that: (1) there is a significant relationship between Critical Thinking and academic compatibility, and (2) no significant differences were found due to gender in each of the critical thinking and academic compatibility variable. هدفت الدراسة الحالية إلى تعرُّف العلاقة بين التفكير الناقد والتوافق الدراسي لدى عينة من طلبة المرحلة الثانوية في مدينة اللاذقية، ومعرفة الفروق في كلٍ من التفكير الناقد والتوافق الدراسي تبعاً لمتغيِّر الجنس، تكوَّنت عينة الدراسة من (90) طالباً وطالبة تمَّ اختيارهم بالطريقة العشوائية الطبقية المتساوية، واستُخدم في الدراسة الحالية أداتان هما: اختبار كورنيل للتفكير الناقد مستوى (X) إعداد إنيس وميلمان وتومكو (Ennis, Millman, &Tomko, 1985)، ومقياس التوافق الدراسي إعداد يونغ مان (Young man) وقنَّنه على البيئة العربية شطة عبد الحميد (2015)، وتوصَّلت الدراسة إلى وجود علاقة ارتباطية موجبة ودالة إحصائياً بين مهارات التفكير الناقد والتوافق الدراسي لدى الطلبة، كما خلصت الدراسة إلى عدم وجود فروق دالة إحصائياً تعزى لمتغيِّر الجنس على كلٍ من اختبار كورنيل للتفكير الناقد، وكذلك مقياس التوافق الدراسي.